Perspectives on climate action and the changing burden of infectious diseases among young Italian doctors and students: a national survey - Francesco Vladimiro Segala; Francesco Vladimiro Segala; Francesco Di Gennaro; Lucia A. A. Giannini; Giacomo Stroffolini; Giacomo Stroffolini; Agnese Colpani; Andrea De Vito; Andrea De Vito; Stefano Di Gregorio; Luisa Frallonardo; Giacomo Guido; et al. (Frontiers Media S.A., 2024)
BackgroundThe eco-climatic crisis has been defined by the World Health Organization as the "single biggest health threat facing humanity," influencing both the emergence of zoonoses and the spread of vector-borne and water-borne diseases. The aim of this survey was to explore knowledge, eco-anxiety and attitudes toward the ecological and climate crisis among young Italian doctors and medical students.MethodsA cross-sectional, multicenter survey was conducted from November 2022 to June 2023, by administering an anonymous questionnaire to Italian doctors and students of medicine. Endpoint of the study was a Knowledge, Attitudes and Practices (KAP) score on ecological and climate crisis (0-20 points). Association between variables and KAP score was assessed by Kruskal-Wallis' or Spearman's test, as appropriate, and significant variables were included into ordinal regression model and reported as adjusted odds ratio (aOR) with their 95% confidence intervals (CI).ResultsBoth KAP and eco-anxiety scores showed acceptable levels of consistency with Cronbach's alpha. A total of 605 medical doctors and students living in 19 Italian regions were included in the study. Median age [Q1-Q3] was 27.6 [24.1-31.3] and females were 352 (58.2%). Despite showing good attitudes toward climate action, knowledge gap were found, with 42.5% (n = 257) of the respondents not knowing the temperature limits set by the Paris Agreements and 45.5% (n = 275) believing that climate change is caused by sunspots. Fears suggestive for eco-anxiety were common. At multivariable ordinal regression, high levels of eco-anxiety (aOR 1.29, p = 0.001) and low trust in government action (aOR 1.96, p = 0.003) were associated with a higher KAP score. Only one Italian medical school offered an educational module on climate change.ConclusionYoung Italian doctors and medical students are concerned about the climate crisis but show poor knowledge of these topics. The Italian academic system should urgently respond to this need.